2018
DOI: 10.7567/jjap.57.04fs06
|View full text |Cite
|
Sign up to set email alerts
|

Guiding principle for crystalline Si photovoltaic modules with high tolerance to acetic acid

Abstract: A guiding principle for highly reliable crystalline Si photovoltaic modules, especially those with high tolerance to acetic acid generated by hydrolysis reaction between water vapor and an ethylene-vinyl acetate (EVA) encapsulant, is proposed. Degradation behavior evaluated by the damp heat test strongly depends on Ag finger electrodes and also EVA encapsulants. The acetic acid concentration in EVA on the glass side directly determines the degradation behavior. The most important factor for high tolerance is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…It has also been noted that this issue seems to be more prevalent in Ag‐screenprinted cells of earlier vintages, and cells manufactured more recently have undergone up to 10 000 h of DH exposure with EVA encapsulant with minimal degradation 18 . Tuning the microstructure of the Ag paste, or replacement of the vulnerable lead oxide with another material (e.g., bismuth oxide), or the introduction of a sacrificial material, may make it less susceptible to corrosion 37,38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been noted that this issue seems to be more prevalent in Ag‐screenprinted cells of earlier vintages, and cells manufactured more recently have undergone up to 10 000 h of DH exposure with EVA encapsulant with minimal degradation 18 . Tuning the microstructure of the Ag paste, or replacement of the vulnerable lead oxide with another material (e.g., bismuth oxide), or the introduction of a sacrificial material, may make it less susceptible to corrosion 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that a non‐permeable backsheet, for example, glass, prevents this degradation, as do non‐EVA encapsulants 16,17 . This degradation seems to affect cells of earlier vintages more than recent vintages, suggesting that recent Ag‐screenprint pastes have been made more tolerant to acetic acid 18 . In all of these studies, it is worth mentioning that degradation is limited to metal components—the underlying cell's antireflection layer, p‐n junction, and wafer are unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…These times correspond to the reacted mass m AA of 52.5 µg for the 70 nm sensors and 120 µg for the 160 nm sensors. Masuda and Hara 16) determined the acetic acid concentration in EVA by ion chromatography during the DH test using the same module without tin sensors [Module C, Fig. 2(b) in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…6 also support this observation, since EL images of both sensors of different thicknesses appear bright until about 2000 h, and the dark region expands from the edges to the central region between 2000 and 4000 h. 29) The dark region is where the current injection is blocked because of the increased contact resistance due to electrode corrosion. 16) Therefore, it is considered to also indicate that a certain amount of acetic acid reacted with the electrode there. Considering this, the advantage of the tin sensor we developed is that acetic acid can be detected both before EL images become dark and after EL darkening saturates, by adjusting film thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation